The Carbon Cost Influences Research on Supply Chain Network Design. Issue 10 (2022) - Li, Bing; Song, Xiang; Wall, Graham; Liu, Xiao
Abstract: In recent years, reducing carbon emissions from the supply chain has become an increasingly important issue. As a result, the necessity and desirability of carbon management has become a key cost element in the supply chain in the future. Supply chain network design is not only an important part of managing the supply chain, but also has a significant impact on carbon emissions. Therefore, this paper formulates a mathematical model to optimize the supply chain network design (SCND), which takes carbon emissions into account. It also reviews the influence of the cost of carbon management on the supply chain network design and then builds a Low Carbon Emission Supply Network Design model for a specific case study. This model helps to enhance the core competitiveness of the supply chain and promote an in-depth analysis of low-carbon supply chain management.